Biomimetic nanomedicines for precise atherosclerosis theranostics - Ying Tao; Xinmiao Lan; Yang Zhang; Chenxing Fu; Lu Liu; Feng Cao; Weisheng Guo (Elsevier, 2023)
Atherosclerosis (AS) is a leading cause of the life-threatening cardiovascular disease (CVD), creating an urgent need for efficient, biocompatible therapeutics for diagnosis and treatment. Biomimetic nanomedicines (bNMs) are moving closer to fulfilling this need, pushing back the frontier of nano-based drug delivery systems design. This review seeks to outline how these nanomedicines (NMs) might work to diagnose and treat atherosclerosis, to trace the trajectory of their development to date and in the coming years, and to provide a foundation for further discussion about atherosclerotic theranostics.